2019
DOI: 10.14740/jocmr3723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching to Azilsartan From Fixed-Dose Combination of an Angiotensin II Receptor Blocker and Calcium Channel Blocker or a Thiazide in Patients With Hypertension

Abstract: Background Despite the availability of antihypertensive treatments, fewer than half of patients who receive treatment successfully achieve blood pressure (BP) goals. The purpose of this study was to evaluate the effect of switching to azilsartan 40 mg from a fixed-dose combination tablet of an angiotensin II receptor blocker (ARB) and amlodipine at 5 mg or azelnidipine at 16 mg (ARB/CCB) or an ARB and hydrochlorothiazide (HCT) at 6.25 mg or 12.5 mg (ARB/HCT) on BP. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… 46 The low dose (2 mg/kg) of azelnidipine was calculated according to the clinical dose. 47 Then our studies showed that azelnidipine inhibited the growth of the PDX model of ESCC in vivo ( Figure 5 ). Furthermore, the azelnidipine group had a similar inhibitory effect in PDX mice compared with the trametinib group in LEG110, another ESCC PDX model.…”
Section: Discussionmentioning
confidence: 86%
“… 46 The low dose (2 mg/kg) of azelnidipine was calculated according to the clinical dose. 47 Then our studies showed that azelnidipine inhibited the growth of the PDX model of ESCC in vivo ( Figure 5 ). Furthermore, the azelnidipine group had a similar inhibitory effect in PDX mice compared with the trametinib group in LEG110, another ESCC PDX model.…”
Section: Discussionmentioning
confidence: 86%
“…The publicly open NIH program announcement (PA-19-034) detailing the classification and identification of 390 understudied druggable genomes was utilized to acquire the list of 261 candidate genes encoding GPCRs and ion channels. The associated literature survey was performed until 9 December 2021, with emphasis on published title words with (1) ion channels since 2017 [4,5,[9][10][11][12][13][14]16,26,27,30,33,[39][40][41][42]44,[46][47][48]53,54,59,61,[69][70][71][72][73][74][75][76][77][78][79][80], (2) ion channel blockers since 2017 [41,[81][82][83][84][85][86][87][88][89][90]…”
Section: Database Literature and Open-access Softwarementioning
confidence: 99%
“…When designing a new drug, some would rather avoid interactions with ion channel proteins, particularly due to cardiovascular safety concerns. Although several attempts have been made to target ion channels, such as K + channel blockers for autoimmune disease [34,35] and antiseizure medications [36][37][38][39][40], and antiarrhythmic treatments [41][42][43][44][45][46], targeting ion channels has resulted in a limited commercialization, as evidenced in the development of Ca 2+ channel blockers for hypertension [47,48]. Nevertheless, a pathway for therapeutic success [49] and significant progress have been achieved with drugs that target Cl − channels, such as cystic fibrosis transmembrane conductance regulator (CFTR) [50].…”
Section: Introductionmentioning
confidence: 99%